Avaliação da influencia da radiação ultravioleta nas propriedades mecânicas do compósito de sisal/poliuretano - Girotto, Thiago (2017)
Polymers derived from petroleum have source of nonrenewable raw material, long time of degradation in the environment and uses solvent in its synthesis. Biodegradable polymers, raw materials from renewable sources is an alternative to these problems, as they do not harm the environment, they do not pose any health risks. Green composites can be used instead of polymer matrix composites reinforced with glass or carbon fibers in some applications. The effects of ultraviolet radiation on polymers will depend on three factors: the radiation dose per unit time and area, temperature and the presence or absence of oxygen. Depending on the dose of the radiation at a given time, there will be the formation of free radicals, then the chain scission or crosslinking, which may affect the mechanical properties. This work aims to study the effect of ultraviolet radiation on the mechanical properties by means of a three - point flexural test of sisal composite with polyurethane polymer matrix derived from oil castor. The fracture surfaces were analyzed using the SEM and the water absorption was measured. The results indicate that the ultraviolet radiation decreases the rupture tension and the swelling after 24 hours was 8%. Composites of sisal fiber, dispersed and woven, can be used in places where they are subject to ultraviolet radiation and a humidity, and a mechanical request as long as they are within the parameters in this work.